ANIMAL WELFARE ASPECTS IN THE RESCUE OF DOGS IN BANJAR TEGAL GRANA AND BANJAR BRAHMANA, SANGEH VILLAGE, ABIANSEMAL DISTRICT, BADUNG REGENCY, BALI - I Gede Kurnia Sandika; I Wayan Masa Tenaya; I Nengah Wandia (Buletin Veteriner Udayana, 2024)
Animal welfare is a condition where animals receive their rights to life, food, freedom of expression, and safety from life-threatening dangers. This research aims to review aspects of animal welfare in Banjar Brahmana and Banjar Tegal Grana, Sangeh Village, Abiansemal District, Badung Regency, Bali, and to examine the dog care practices in these two banjars, with data collected door-to-door through questionnaires. The study examined the compatibility of dog care practices by the community in both banjars with the concept of the five freedoms for animals. It was found that, overall, the principles of animal welfare were implemented by dog-owning households in Banjar Brahmana and Banjar Tegal Grana, with the following percentages for the application of the five freedoms: freedom from discomfort: 97.7% in Banjar Brahmana and 100% in Banjar Tegal Grana, freedom from hunger: 94.8% in Banjar Brahmana and 91.8% in Banjar Tegal Grana, freedom to express natural behavior: 78.4% in Banjar Brahmana and 78.8% in Banjar Tegal Grana, freedom from fear and distress: 90.7% in Banjar Brahmana and 88.6% in Banjar Tegal Grana, and freedom from pain, injury, and disease: 81.4% in Banjar Brahmana and 80.4% in Banjar Tegal Grana. Overall, the assessment of animal welfare implementation based on the five freedoms principle scored an average of over 50% in each principle, indicating that both banjars have implemented animal welfare aspects for the dogs kept in Banjar Brahmana and Banjar Tegal Grana.